Level of Online Media Literacy of Collegiate Students: Basis for a Proposed Curriculum Enhancement Program - Riparip, Eduard; Caballes, Dennis (Journal of Interdisciplinary Perspectives, 2024)
As early as the 2000s, the growing demand to integrate digital skills as competencies into the curriculum has been widely advocated by media scholars (Hobbs, 2009; Hobbs & Jensen, 2013; Bautista, 2021). Among these digital skills is online media literacy, which, according to Hallaq (2016), impacts students’ acquisition of knowledge. Media literacy is defined as “the ability to access, analyze, evaluate, and create messages across a variety of contexts" (Livingstone, 2004). The five components of online media literacy formulated by Hallaq (2016) used in this study are ethical awareness, media access, media awareness, media evaluation, and media production. This study aimed to assess the level of online media literacy of Centro Escolar University-Makati students based on Hallaq's Digital Online Media Literacy Assessment (DOMLA). Using convenience sampling, 374 college students participated in the survey. Data collected were analyzed using statistical tools such as frequency, weighted mean, and the Kruskal-Wallis Test. The findings revealed that the students are slightly online media literate. Specifically, they are literate in ethical awareness and media awareness. The results also indicated no significant difference in the level of online media literacy across different ages and year levels, suggesting that media literacy is consistently moderate across different demographics. The study recommends a contextualized and interactive digital media literacy curriculum in college, which could either be separate and independent or integrated into various general education and professional subjects. Additionally, universities are encouraged to adopt the Vowel Approach in Online Media Literacy (awareness, education, integration, optimization, and utilization) formulated by the researchers.